Natural History from Appendiceal Mucocele to Jelly Belly - Hoskovec, David; Krška, Zdeněk; Pudlač, Adam; Lochman, Matyáš; Strohalmová, Sabina; Bocán, Andrej; Koželský, Pavel; Dytrych, Petr (Diagnostics (Basel, Switzerland), 2024)
Mucocele of the appendix and pseudomyxoma peritonei are rare diseases. The clinical findings are nonspecific in the early stages of the disease. The sequelae of appendiceal mucocele, its perforation, and extensive peritoneal involvement via pseudomyxoma peritonei (jelly belly) are repeatedly described in the literature. We present the typical findings in the natural history of the disease.
Keywords: pseudomyxoma peritonei; mucocele; cytoreductive surgery; HIPEC; jelly belly